Analisis Putusan Banding Pengadilan Pajak Sengketa Nilai Pabean: Studi Kasus di KPU BC Tipe A Tanjung Priok - Ahmad Sholihin; Siti Nuryanah (Universitas Jember, 2024)
This study aims to evaluate and mitigate the factors causing the low victory of KPU BC Type A Tanjung Priok in the customs value dispute at the Tax Court. This study is qualitative with triangulation method of content analysis and interview. Data is obtained from the tax court decision on the customs value dispute for the period 2018 to 2020. The study found that factors that cause the low winnings on customs value disputes are the low effectiveness of collecting transaction evidence at the time of objection and the limitations of testing the validity of the evidence submitted by the Appellant during the appeal hearing process. This study provide a practical implication that KPU BC Type A Tanjung Priok can conduct further action to mitigate the loss of the appeal hearing for the customs value dispute by for example optimizing data requests to the applicant during the objection process, coordinating with the Document Examiner Officer (Pejabat Fungsional Pemeriksa Dokumen - PFPD) to improve the objection decision, and evaluating tax court decisions. Keywords: Tax Dispute, Tax Court, Tax Appeal, Customs